An Investigation into Self-Regulated Learning in a Virtual Classroom: A Higher Education Perspective (Global Journal of Human-Social Science, 2021)
In the wake of the global pandemic and restrictions on human-to-human contacts, higher education institutions have turned to e-learning as a solution to keep teaching and learning going. Indeed, aside from allowing the continuation of education during situations like that, the other argument supporting e-learning is because of its social constructivist pedagogy and effective self-regulated learning. However, the claim of self-regulated learning in the context of e-learning has not empirically been validated. Thus, based on responses from 116 individuals, using a mixed-method approach, we sought to evaluate the effect of the use of the Learning Management System on students' self-regulated learning. Our findings indicate that despite the advantages of convenience and access to materials provided, the system did not appear to regulate students learning with significant challenges of unreliable internet connectivity, lack of key functionalities and features ultimately impeding optimal use. The study discusses these findings and draws implications for theory and practice.
Keywords: self-regulated learning; learning management system; university students